Development of the national cybersecurity system of Ukraine as a necessary element of information society development - S. H. Petrov (Bulletin of Kharkiv National University of Internal Affairs)
The article examines modern development problems of the national cybersecurity system of Ukraine. With the emergence of new challenges and threats in cyberspace, there is a need to find new methods and ways to combat cybercrime and cyberterrorism. The current state of the fight against cybercrime in Ukraine and the prospects for capacity building and reform of the main subjects in cybersecurity in Ukraine are outlined.